Physiological and neuromuscular response to a distance sprint triathlon competition. Influence of age and athletic level (Revista horizonte, 2021)
Objective: This study aimed to describe the acute impact of a simulated sprint-distance triathlon at physiological and neuromuscular levels and to determine whether age and athletic performance influenced the response in triathletes. Methods: Nineteen triathletes performed a sprint-distance triathlon under simulated conditions. Cardiovascular response was monitored during the race. Rate of perceived exertion along with muscularperformance parameters (countermovement jump [CMJ], squat jump [SJ], and handgrip strength test [HS]) were tested at pre-and posttest and during every transition, while a 20-m sprint test (S20m) was performed before and after the race. Blood lactate was recorded postrace. Results: A repeated measures analysis of variance showed that the neuromuscular response—in terms of CMJ, SJ, and HS—was unchanged (p≥0.05), while S20m performance was impaired at posttest (p